Effects of Early Literacy Promotion on Child Language Development and Home Reading Environment: A Randomized Controlled Trial - James P. Guevara, MD, MPH; Danielle Erkoboni, MD; Marsha Gerdes, PhD; Sherry Winston, MS; Danielle Sands, MPH; Kirsten Rogers, BS; Trude Haecker, MD; Manuel E. Jimenez, MD, MSHP; Alan L. Mendelsohn, MD (Elsevier, 2020)
Objective: To determine if early literacy promotion, which consisted of board books and reading promotion beginning with newborns, is more effective than standard literacy promotion beginning at 6 months. Study design: Hybrid type 1 randomized controlled implementation trial of Medicaid-eligible newborns. Prior to 6 months of age, early literacy promotion participants received board books and reading promotion at well visits plus weekly text messages on reading, while standard literacy promotion participants only received weekly text messages on safety. Both groups received board books and reading promotion at well visits after 6 months as part of Reach Out and Read. Measures included proportion who received board books to assess implementation and StimQ Read Subscale (SQRS) scores and Preschool Language Scale-Fifth Edition (PLS-5) scores at 6 and 24 months to assess outcomes. Differences in measures were assessed using intention-to-treat analysis. Results: Of 120 newborns enrolled, most were African American, resided with a single parent, or had a parent with ≤high school education. Overall 82% of early literacy promotion participants received books/counseling at well visits <6 months old. Children in the early literacy promotion arm had greater SQRS scores (11.0 vs 9.4, P = .006) but similar PLS-5 scores at 6 months, but there were no differences in SQRS or PLS-5 scores between groups at 24 months. Conclusions: Implementation of a literacy promotion program early in infancy was associated with richer home reading environments at 6 months but did not improve language development. Although an early literacy program was feasible, additional study may be needed to assess other potential benefits. Trial registration: Clinicaltrials.gov: NCT02713659.